Assessing the financial and financing conditions of firms in Europe: the financial module in CompNet - Annalisa Ferrando; Carlo Altomonte; Sven Blank; Philipp Meinen; Matteo Iudice; Marie-Hélène Felt; Katja Neugebauer; Iulia Siedschlag (European Central Bank (ECB), 2015)
This paper provides an encompassing description of the various indicators compiled in the financial module of CompNet using balance sheet information of European firms. We investigate whether and to which extent the heterogeneous financial positions of firms have affected firms' investment decisions, especially during the recent crisis. Our results confirm the relevance of leverage for investment, in addition to other common determinants, such as cash flow or sales growth. In particular, we find evidence that higher levels of indebtedness act as a drag on investment. We investigate cash holding policies and find significant differences across firm sizes and degrees of financial constraints. Furthermore, our data confirm the pro-cyclicality of firm profitability and its negative association with financial constraints. Finally, we exploit the richness of this new dataset to document the relationships between firms' financial and financing conditions and their productivity.
Keywords: D22; D24; D92; G32; 330; firm financing conditions and constraints; firm heterogeneity; productivity